Shewanella putrefaciens Fish pathogenic strains contain plasmids that are absent in the probiotic strain s. Putrefaciens pdp11 - Pérez-Gómez, Olivia; Domínguez-Maqueda, Marta; Grande-Pérez, Ana; Esteve, Consuelo; Seoane, Pedro; Tapia-Paniagua, Silvana Teresa; Balebona-Accino, María del Carmen; Moriñigo-Gutiérrez, Miguel Ángel (Aquaculture europe congress, 2022)
Probiotics are live microorganisms that confer a health benefit to the host when administered in adequate amounts. Shewanella putrefaciens Pdp11 has been described as a probiotic for farmed fish species such as Solea senegalensis and Sparus aurata. In contrast, other strains of S. putrefaciens have been described as pathogenic for other cultured fish damage of the mouth, extensive skin discoloration, exophthalmia, ascites and bad odour. The S. putrefaciens group was recovered from freshwater samples taken at the L′Albufera system, along autumn– winter 2015. Its counts significantly increased in freshwater parallel to hypoxia and temperature rising. Shewanellae strains were identified as S. putrefaciens and S. xiamenensis by 16S rRNA gene sequencing. These isolates recovered from sick eels or freshwater were virulent for European eel by IP challenge (LD50 106 CFU g−1 body weight. The plasmids plays an important role in the genes transfer and insertion then there can been implicated in antibiotics resistance, degradative pathway and pathogenicity characteristics. The genetic variation conducted by plasmid could induce an impact in probiotic proprieties. In this research, we searched the present or absent of plasmids in pathogenic and probiotic strains of S. putrefaciens. As well as, this plasmids implication in development of virulence factors. The probiotic strain S. putrefaciens Pdp11 did not present plasmid, which was only found in two of the five pathogenic strains. The results allowed us to discard the probiotic Pdp11 could present a pathogenic characteristic as the TA type II system as a virulence factor and its self-regulating characteristics, which may be behind its probiotic nature, making the Pdp11 strain unique in comparison to other S. putrefaciens strains.
Keywords: Acuicultura - Patógenos; Plasmid; Pathogenic strains; Probiotic strain